The Effect of Mobilization Combined with Soft Tissue Massage Versus Soft Tissue Massage Alone on Migraine Intensity - Zahid, Ambreen; Sagheer, Basita; Mubeen, Iqra; Mutasansar, Alishba; Amin, Fatima (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Mobilization methods have shown optimistic results for the treatment of migraine, however previous studies also show unavailability of control group, or subjected to deficient methodological quality. Aim: To differentiate the effects of cervical mobilization coupled with massage versus massage only on, headache frequency, intensity and disability in patients with migraine. Methodology: A Randomized, single-blinded, controlled clinical trial was conducted in Izmir Medicare center. Subjects with migraine headache were selected and were divided into two groups: 1) Mobilization and massage (case) 2) Massage only (control). Four sessions of treatment was given in four weeks. Headache disability inventory (HDI) was evaluated before at baseline and after completion of treatment sessions. Results: Study shows that cervical mobilization is effective treatment for migraine .according to result analysis both groups shows high improvement in score of HDI before and after treatment. Additionally, if compare with control group patient that receive additional treatment shows no significant results in reduction of migraine frequency among all data points. Conclusion: This study shows positive results of treatment for migraine. Both interventions massage alone and massage with cervical mobilization showed positive results for migraine. Furthermore massage with mobilization shows more effective and positive results than alone massage on the four sub-components of HDI.